2016
DOI: 10.1371/journal.pone.0167501
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cognitively Engaging Exergame-Based Physical Activity Enhances Executive Functions in Adolescents

Abstract: The study aimed to elucidate the influence of cognitive engagement comprised in an acute bout of exergame-based physical activity on executive functions (inhibition, cognitive flexibility) in adolescents. Therefore, the level of cognitive engagement and the intensity of physical activity were systematically varied across three experimental conditions. Sixty-five healthy male adolescents (13–16 years) were randomly assigned to one of three conditions: (a) physical activity with high levels of cognitive engageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(116 citation statements)
references
References 62 publications
2
91
1
7
Order By: Relevance
“…As can be seen from these examples, the workouts mainly include a training of strength, coordination (and endurance), as well as demands on cognitive functions such as inhibition, switching, updating, attention, and speed of action. In two previous studies, this exergame has been shown to be cognitively and physically challenging, and acute effects on the EFs have been reported . Moreover, it has been compared to purely physically challenging aerobic exergaming and was found to be more cognitively challenging than the latter …”
Section: Methodsmentioning
confidence: 96%
“…As can be seen from these examples, the workouts mainly include a training of strength, coordination (and endurance), as well as demands on cognitive functions such as inhibition, switching, updating, attention, and speed of action. In two previous studies, this exergame has been shown to be cognitively and physically challenging, and acute effects on the EFs have been reported . Moreover, it has been compared to purely physically challenging aerobic exergaming and was found to be more cognitively challenging than the latter …”
Section: Methodsmentioning
confidence: 96%
“…The Centers for Disease Control and Prevention (CDC, 2015) has publicly recognized that physical activity may support academic behavior (i.e., timeon-task) and classroom focus, and these gains occur independently of weight status (Davis, Tkacz, Tomporowski, & Bustamante, 2015). One session of physical activity can improve attention Janssen, Toussaint, van Mechelen, & Verhagen, 2014b;Pontifex, Scudder, Drollette, & Hillman, 2012), increase working memory (Benzing, Heinks, Eggenberger, & Schmidt, 2016;Pontifex, Hillman, Fernhall, Thompson, & Valentini, 2009), enhance academic learning time (Bartholomew & Jowers, 2011;Webster, Wadsworth, & Robinson, 2015), and improve the development of anterior frontal brain patterns that support task completion and lesson comprehension (Chaddock-Heyman et al, 2013).…”
Section: The Effect Of Physical Activity On Behaviormentioning
confidence: 99%
“…These video games have raised a lot of clinical interest over the past decade, both as commercially available video games (used within an evidence-based neuropsychological framework), or specifically designed serious games. Exergames have been used to train many executive functions (13,14), and, as pointed out by a recent meta-analysis (15), they have been used to improve cognitive functioning in neurological disabilities of older adults or school-aged children affected by developmental disorders (16,17). They also increase daily physical activity in populations such as children with autism, without whom may have difficulty accessing collective sports (18).…”
Section: Introductionmentioning
confidence: 99%